Topics in nonlinear dynamics, volume 1 : proceedings of the 31st IMAC, a conference on structural dynamics, 2013 - Adams, Douglas; Carrella, Alex; Kerschen, Gaetan (Conference Proceedings of the Society for Experimental Mechanics Series, 2013)
Topics in Nonlinear Dynamics, Volume 1: Proceedings of the 31st IMAC, A Conference and Exposition on Structural Dynamics, 2013, the first volume of seven from the Conference, brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on fundamental and applied aspects of Structural Dynamics, including papers on:   Nonlinear Oscillations Nonlinearities In Practice Nonlinear System Identification: Methods Nonlinear System Identification: Friction & Contact Nonlinear Modal Analysis Nonlinear Modeling & Simulation Nonlinear Vibration Absorbers Constructive Utilization of Nonlinearity